Female economic participation with information and communication technology (ICT) advancement: Evidence from Sub-Saharan Africa - Uchenna Rapuluchukwu Efobi; Belmondo Tanankem Voufo; Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
This study complements existing literature by investigating how the advancement in information and communication technology affects the formal economic participation of women. The focus is on 48 African countries for the period 1990-2014. The empirical evidence is based on Ordinary Least Squares, Fixed Effects and the Generalized Method of Moments regressions. The results show that improving communication technology increases female economic participation with the following consistent order of increasing magnitude: mobile phone penetration; internet penetration, and fixed broadband subscriptions. The findings are robust to the control for heterogeneities across countries. Policy implications are discussed.
Keywords: G20; I10; I32; O40; O55; 330; Africa; Gender; ICT; Inclusive development; Technology